Ethnography and folklore of the Yakuts in the works of A. E. Kulakovsky in the context of textology - Sivtceva-Maksimova, Praskovia (2020)
The relevance of the present investigation is revealed in the study of the works introduced in terms of textology in the works of the poet A. E. Kulakovsky. The analysis of the conceptual conclusions, related to the culture of the Sakha people, provides the substantiation of the new facts of the biography and personality of the writer, who performed a special historical mission in the spiritual life of the society.Therefore, the objective of the study is to expand the parameters of the scientific argumentation of the analyzed texts of Kulakovsky, in order to reveal the meaning of his first publications. The authors of the present investigation apply cultural and hermeneutical methods of philology in the context of the comparative typological analysis of texts, sources and documents.The results of the study suggest the confirmation of Kulakovsky's concept of discourse as narrative, introduced in his works on ethnography and folklore. The systematization of the writings of the mentioned author is situated at the intersection of the problems of linguistics, cognitive psychology and sociology. It is worth noting that the presence of the practical elements of Christian culture in the beliefs of Sakha and in the work of Kulakovsky.